2012
DOI: 10.1021/pr200796a
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomic and Metabolomic Analysis of Larval Brain Associated with Diapause Induction and Preparation in the Cotton Bollworm, Helicoverpa armigera

Abstract: Diapause is a developmental arrest that allows an organism to survive unfavorable environmental conditions and is induced by environmental signals at a certain sensitive developmental stage. In Helicoverpa armigera, the larval brain receives the environmental signals for diapause induction and then regulates diapause entry at the pupal stage. Here, combined proteomic and metabolomic differential display analysis was performed on the H. armigera larval brain. Using two-dimensional electrophoresis, it was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 58 publications
(89 reference statements)
3
50
0
Order By: Relevance
“…Thirty brains of each sample were extracted and derivatized as described (22). In brief, each sample was homogenized in a 600 μL methanol-chloroform mixture (2:1) and sonicated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty brains of each sample were extracted and derivatized as described (22). In brief, each sample was homogenized in a 600 μL methanol-chloroform mixture (2:1) and sonicated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The GC-MS analysis program was described (22) and slightly modified. The 1 μL derivatization sample was autoinjected using a 1:10 split ratio to a Trace GC Ultra-DSQ II GC-MS (Thermo), with the injector temperature held at 280°C.…”
Section: Gc-ms Analysis For Metabolitesmentioning
confidence: 99%
“…Answers to this question will only come from more detailed investigations to characterise downstream (effector) and upstream (regulatory) mechanisms. This has begun to some extent with investigations of diapause induction, initiation and termination in the cotton bollworm, Helicoverpa armigera, and a key role for metabolic change has been identified in regulating the diapause programme Zhang et al, 2012). Thus, while it is apparent that compatible solutes such as sugars, free fatty acids and polyols can protect cells both osmotically (Kostál et al, 2001) and by stabilising membranes and macromolecules even at low physiological concentrations, we still lack a detailed understanding of the precise functional role(s) that most cold-responsive metabolites play, or the stress response regulatory cascades that induce them.…”
Section: Reviewmentioning
confidence: 99%
“…This clearly masks any subtleties arising from tissue-specific responses and frustrates further any understanding of regulatory mechanisms controlling metabolite responses to cold. In this respect, investigations of diapause are again at the vanguard, and tissue-specific metabolomic studies have identified clear differences in fat body, brain and haemolymph profiles (Zhang et al, 2012). A more interesting issue is the extent to which metabolite responses are initiated centrally but implemented in peripheral tissues.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation